Orbital mechanics for engineering students - Curtis, Howard D (Elsevier Butterworth Heinemann, 2012)
Orbital Mechanics for Engineering Students is a foundation text for this cornerstone aerospace subject. It offers a rigorous and contemporary introduction to the physical phenomena and analytical procedures required to understand and predict the behavior of orbiting spacecraft. Structured to cover the requirements of one and two semester courses in orbital mechanics, it is also a springboard to more advanced study." "Written for undergraduate students of aerospace engineering, astronautical engineering, engineering mechanics and engineering physics who have completed first courses in physics, vector dynamics and mathematics (through to differential equations and linear algebra), it will also be appropriate for graduate students new to the subject. The book otherwise assumes no previous experience and is self-contained. All of the required basic dynamics principles are developed in detail so that neither student nor instructor will have to refer to other sources